Arquitectura FPGA para Simulación de Aprovisionamiento de Alimentos en Colonias de Hormigas Artificiales - Rodríguez Rodríguez, Cristian David; Melgarejo Rey, Miguel Alberto (Ingeniería, 2015)
This paper presents some results regarding the desing and implementation of an architecture that supports an experimental platform for simulating the foraging process of ant colonies. Both the Ant-System and the Ant-Cycle algorithms model the behavior of ants. The platform allows to change parameters like the quantity and speed of ants, the amount and location of food and the ratio and difussion frequency of ant pheromone. These parameters are visualized through a VGA interface. The hardware implementation is carried out over FPGA Xilinx© technology. Theory behind this design considers that complex behaviors can emerge from systems with simple structure. This work confronts the question about global complexity emerging from a system whose structural complexity is minimal or inexistent.